Theories on the impact of weather on consumer spending and retail sales - Ivana Štulec (Tržište, 2013)
Weather affects four basic purchasing decisions: what, when, where and in what quantity to buy. Even though retail is not traditionally perceived to be a weather sensitive sector, results of studies show that weather has a significant impact on store traffic and sales of numerous product categories. The paper outlines theories on the effects of weather on consumer spending and retail sales, and gives an overview of the results of former relevant research studies. It can be concluded that the impact of weather on consumer spending and retail sales is not uniform, but that it varies depending on the month of the year, product category and store format. Therefore, further studies on weather sensitivity and weather risk in retail are necessary. The purpose of this paper is to help raise awareness of weather risk in retail, and to provide a firm foundation for future research on weather sensitivity and weather risk in retail.